IMPLEMENTASI MEDIA VIDEO INTERAKTIF DALAM MATA PELAJARAN Al-QUR’AN DAN Al-HADITS DI MI DARUT TAQWA SENGONAGUNG PURWOSARI PASURUAN - Anang sholikhudin (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2020)
Interactive Video Media in learning is a living image which is a picture in a frame where frame by frame is mechanically projected through the projector lens so that the screen looks alive. As with films, videos can depict an object moving together with natural sounds or sounds that are appropriate in learning. The formulation of the problems in this study are: 1. How is the implementation of interactive video media in the subject of al-Qur'an and al-Hadith at MI Darut Taqwa Sengonagung Purwosari Pasuruan? 2. What factors support and hinder the implementation of interactive video media in the subject of al-Qur'an and al-Hadith at MI Darut Taqwa Sengonagung Purwosari Pasuruan ?. The purpose of this study was to determine the implementation of interactive video media in the subject of al-Qur'an and al-Hadith and to determine the supporting and inhibiting factors for implementing interactive video media in the subjects of al-Qur'an and al-Hadith at MI Darut Taqwa Sengonagung Purwosari Pasuruan. . Data collection was carried out through observation, interviews, and documentation to get a complete picture and understanding of the two selected research focuses. The results showed (1) the implementation of interactive video learning at MI Darut Taqwa shows that learning using learning methods and media is quite flexible. This means that it is adjusted to the conditions of students. The learning method developed in the Interactive Video media learning is the question and answer method, the discussion method, and the demonstration method. (2) Supporting Factors for the Implementation of Interactive Video Media in Al-Qur'an and Al-Hadith Subjects at MI Darut Taqwa Sengonagung Purwosari Pasuruan Is: interactive video media makes it easy for students to understand lessons, using interactive video media of students' attention and interest very effective. While the inhibiting factor is that in implementing interactive video media the teacher requires time and careful preparation, so it requires a lot of time, too much media if you maximize learning interactive video media in the classroom.